Housewives' Perceptions of Communication Styles in Greeting Interactions on Facebook Pro - Rahmania, Afifah; Sazali, Hasan (Program Pascasarjana UIN Sumatera Utara, 2025)
Social media has become a new space for housewives to build social interactions. Facebook Pro, as one of the platforms designed to provide space for its users such as housewives to discuss, share information, and greet each other. The purpose of this study was to determine the perception of housewives towards the communication style and form of greeting interactions that occur on Facebook Pro. This study uses a qualitative method with in-depth interview techniques to five housewife informants who actively interact on Facebook Pro content. By using Symbolic Interaction Theory, which views interaction as a process of forming meaning through social symbols. The results of the study show that a warm, polite, and non-patronizing communication style is preferred because it is interpreted as a symbol of closeness, support, politeness, and a binder of the identity of Facebook Pro content creators and also makes Facebook Pro accounts increasingly well-known and has the opportunity to monetize accounts.